Going to scale with ICTs for agriculture: Stories from the field - Willmott-Harrop, Elizabeth; Pye-Smith, Charlie (Technical Centre for Agricultural and Rural Cooperation, 2017)
The huge potential of ICTs for agriculture (ICT4Ag), from increasing agricultural yields to helping farmers get a fairer price for their produce, is well documented. Technologies such as SMS applications, mobile banking and satellite data have been used successfully to give agricultural stakeholders access to farm mapping, weather data, marketing tools, financial credit, advice from extension workers, and social networks, among other things. These technological applications are capable of reaching hundreds of millions of smallholder farmers and stakeholders in rural areas, acting as a catalyst for positive change and in achieving the SDGs. However, limits on their reach include poor internet connectivity in the rural areas of developing nations, high illiteracy rates among smallholder farmers and fishers, and the inability of pilot projects to go to scale due to lack of long-term funding or not having measures for their sustainability built into the programme design. This booklet will inspire agricultural stakeholders around the world – from the smallholder farmer to governments and their international trading partners – to further realise the remarkable change that ICTs can effect in the lives of rural and farming communities.